EVALUASI 35 TAHUN (1970 – 2005) PENGELOLAAN HUTAN ALAM DI KALIMANTAN TIMUR - ni, Daro (Jurnal Borneo Administrator, 2006)
In the New Order era, forest management and utilization in East Kalimantan does not assure the sustainability of wood production. Forest has tended to be depleted and degraded instead, characterized by lack of special kinds of wood and change in forest structure due to uncontrolled deforestration. In this sense, natural forest could be beneficially managed if expected value in the long term equal to current value. This is the importance of local government capital share in the forest management. Apart of that, forest management in the previous period has contributed to the creation of labor market and income generation for the worker. However, there seems to be factual that forest industry was unable to produce tricle down effect for the people lived surround the forest. This paper tries to evaluate the policy and practice of forest management during New Order and Reform era, particularly in line with the effort of promoting social welfare in East Kalimantan.Keywords: Pengelolaan hutan lestari, Kalimantan Timur.